Special issue - The asbestos war (International Journal of Occupational and Environmental Health, 2003)
"That asbestos is still being sold despite overwhelming evidence linking it to debilitating and fatal diseases is testament to the effectiveness of a campaign, spearheaded by Canadian interests, to promote a product already banned in many developed countries. Blessed by government and commercial support, asbestos apologists have implemented a long-term coordinated strategy targeting new consumers in Asia, the Far East and Latin America. At industry-backed “conferences” and on government-funded junkets, they spin a web of deceit, telling all who will listen that “chrysotile (white asbestos) can be used safely.” The fact that Canada exports over 95% of all the chrysotile it mines suggests that while chrysotile is supposedly safe enough for foreigners, it is not safe enough for Canadians. Asbestos victims in many countries have struggled to gain public recognition of the human cost of asbestos use. In recent years, nongovernmental organizations working with these groups have created a global anti-asbestos virtual network; with the commitment and support of thousands of “virtual members,” this network challenges industry’s propaganda and exposes the forces that support its cynical attempt to offload this dangerous substance on developing countries. ..."